Interrupting prolonged sitting with brief bouts of light walking or simple resistance activities reduces resting blood pressure and plasma noradrenaline in type 2 diabetes. Issue 12 (December 2016) - Dempsey, Paddy C.; Sacre, Julian W.; Larsen, Robyn N.; Straznicky, Nora E.; Sethi, Parneet; Cohen, Neale D.; Cerin, Ester; Lambert, Gavin W.; Owen, Neville; Kingwell, Bronwyn A.; Dunstan, David W.
Abstract : Objective: Prolonged sitting is increasingly recognized as a ubiquitous cardiometabolic risk factor, possibly distinct from lack of physical exercise. We examined whether interrupting prolonged sitting with brief bouts of light-intensity activity reduced blood pressure (BP) and plasma noradrenaline in type 2 diabetes (T2D). Methods: In a randomized crossover trial, 24 inactive overweight/obese adults with T2D (14 men; mean ± SD; 62 ± 6 years) consumed standardized meals during 3 × 8 h conditions: uninterrupted sitting (SIT); sitting + half-hourly bouts of walking (3.2 km/h for 3-min) (light-intensity walking); and sitting + half-hourly bouts of simple resistance activities for 3 min (SRAs), each separated by 6–14 days washout. Resting seated BP was measured hourly (mean of three recordings, ≥20-min postactivity). Plasma noradrenaline was measured at 30-min intervals for the first hour after meals and hourly thereafter. Results: Compared with SIT, mean resting SBP and DBP were significantly reduced ( P  < 0.001) for both light-intensity walking (mean ± SEM; −14 ± 1/−8 ± 1 mmHg) and SRA (−16 ± 1/−10 ± 1 mmHg), with a more pronounced effect for SRA ( P  < 0.05 versus light-intensity walking). Similarly, mean plasma noradrenaline was significantly reduced for both light-intensity walking (−0.3 ± 0.1 nmol/l) and SRA (−0.6 ± 0.1 nmol/l) versus SIT, with SRA lower than light-intensity walking ( P  < 0.05). Mean resting heart rate was lowered by light-intensity walking (−3 ± 1 bpm; P  < 0.05), but not SRA (−1 ± 1 bpm). Conclusion: Interrupting prolonged sitting with brief bouts of light-intensity walking or SRA reduces resting BP and plasma noradrenaline in adults with T2D, with SRA being more effective. Given the ubiquity of sedentary behaviors and poor adherence to structured exercise, this approach may have important implications for BP management in patients with T2D. Abstract : Supplemental Digital Content is available in the text